Effects of polydispersity on PGSE NMR coherence features - Yadav, Nirbhay N.; Price, William S. (Diffusion Fundamentals, 2007)
Real systems always contain some degree of polydispersity and yet the effects of this real and very important problem have not been studied in great detail in NMR diffusion experiments. The effects of polydispersity become even less clear when we are outside the short gradient pulse (SGP) limit (which we generally are). Here we investigate the effects of polydispersity, in the form of a Gaussian distribution of characteristic distances, on the coherence features of PGSE NMR experiments of a model system. Characteristic pore sizes were determined from the coherence features and compared to characteristic distances determined from Fourier transforms of the second derivative.